Effect of Foliar Application of Some Micronutrients at Two Growth Stages on Growth, Yield and Yield Components of Two Bread Wheat (Triticum aestivum L.) Varieties - Dilan R. Hadi; Tareeq H. Kreem; Bahar J. Mahmood (Zanco Journal of Pure and Applied Sciences, 2020)
A field experiment was conducted during the growing season of 2018-2019 at the experimental farm of the college of Agricultural Engineering Sciences/ Salahaddin University- Erbil (Latitude 36 ̊4 N and Longitude 44 ̊2 E) to study the effect of Zn, Fe foliar application and their combination at two growth stages on growth and yield of two wheat varieties (Triticum aestivum L.). A factorial experiment (2×2×4) was conducted using randomized complete block design (RCBD) with three replicates. The research was included two wheat varieties (Hawler 2 and Hawler 4), foliar fertilization at two growth stages (Tillering GS Z25 and booting GS Z45) and four fertilizers treatments which include F1(control), F2 (134 mg/L) Fe as (FeSO4.7 H2O), F3 (270.01 mg/L Zn) as ZnSO4 and F4 ((134 mg/L Fe + 270.01 mg/L Zn) combination of (F2.7H2O + ZnSO4). The results indicated that the treatment combination of V1 × S2 × F0 recorded highest values for no. of spike plant-1, no. of spikelet spike-1 and no. of seed spike-1 (4.25, 51.51 and 54.27) respectively. While the highest seed weight spike-1, seed index (22.71and 45.41) were recorded for the combination treatment of V1 × S1 × F4 the results also revealed that the treatment combinations (V2 × S1 × F4) and (V1 × S1 × F1) offered the highest and lowest seed yield respectively. The treatment combinations (V2 × S1 × F4) resulted in higher seed yield by 69% compared to (V1 × S1 × F1).